2019
DOI: 10.1530/ec-19-0348
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of brain glucose uptake by PET in obesity and cognitive dysfunction: life-course perspective

Abstract: The prevalence of obesity has reached epidemic proportions and keeps growing. Obesity seems implicated in the pathogenesis of cognitive dysfunction, Alzheimer’s disease and dementia, and vice versa. Growing scientific efforts are being devoted to the identification of central mechanisms underlying the frequent association between obesity and cognitive dysfunction. Glucose brain handling undergoes dynamic changes during the life-course, suggesting that its alterations might precede and contribute to degenerativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 115 publications
(180 reference statements)
0
19
0
Order By: Relevance
“…Regarding the insulin effect, seminal work by Talbot et al ( 12 ) showed normal activation of the insulin-signaling pathway in ex vivo studies in cognitively normal brains and brains with MCI under normal and supraphysiologic insulin levels, and of insulin resistance in AD brain slices. Accumulating evidence supports the notion that AD may be considered a metabolic disease of the brain, in which brain glucose use is impaired and, whereas early brain glucose hypermetabolism (i.e., MCI) may be considered a compensatory phase to the initial neurodegenerative insult, this compensation may eventually accelerate the degenerative process and ultimately lead to brain hypometabolism ( 33 ). Similar temporal paradoxical patterns have been described in other neuroimaging studies, in which memory-related functional MRI showed hyperactivation in less-impaired patients with MCI and hypoactivation in more-impaired patients with MCI ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the insulin effect, seminal work by Talbot et al ( 12 ) showed normal activation of the insulin-signaling pathway in ex vivo studies in cognitively normal brains and brains with MCI under normal and supraphysiologic insulin levels, and of insulin resistance in AD brain slices. Accumulating evidence supports the notion that AD may be considered a metabolic disease of the brain, in which brain glucose use is impaired and, whereas early brain glucose hypermetabolism (i.e., MCI) may be considered a compensatory phase to the initial neurodegenerative insult, this compensation may eventually accelerate the degenerative process and ultimately lead to brain hypometabolism ( 33 ). Similar temporal paradoxical patterns have been described in other neuroimaging studies, in which memory-related functional MRI showed hyperactivation in less-impaired patients with MCI and hypoactivation in more-impaired patients with MCI ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…Imaging of brain glucose by positron emission tomography is a standard method for assessing brain metabolism in vivo. Lozzo et al’s (2019) review [ 43 ] assessed studies that employed this technique in attempts to reveal the underlying mechanisms that link obesity and cognitive dysfunction. They concluded that brain hypermetabolism is associated with cognitive control for food rewards, low BDNF levels, and insulin resistance.…”
Section: Risk Factorsmentioning
confidence: 99%
“…In addition, frontotemporal brain regions were registered to show decreased brain glucose uptake in type 2 diabetic individuals, even after controlling for different vascular risk factors [27]. While some studies indicated higher fasting cerebral metabolism in obese patients compared to lean people, others pointed out no associations between obesity and brain glucose uptake [17,28]. The underlying mechanism behind cerebral metabolic changes related to metabolic diseases is not exactly known.…”
Section: Discussionmentioning
confidence: 99%